Functional assessment of foot and ankle tendinopathies treated with tendoscopy - Huyer, Rodrigo Guimarães; Cillo , Mário Sérgio Paulillo; Castro Filho , Carlos Daniel Cândido; Bertelli , Hallan Douglas; Berg, Renato Morelli (Journal of the Foot & Ankle, 2021)
Objective: To assess postoperative clinical functional outcomes, based on the American Orthopaedic Foot & Ankle Society (AOFAS) score, of tendoscopies performed in the treatment of foot and ankle pathologies. Methods: Our comparative assessment used AOFAS scores obtained preoperatively and at early and late postoperative stages - 1 month and 6 to 12 months after surgery - of 14 patients with foot and ankle tendinopathies. These included peroneal tendon dislocation, peroneal tendonitis, and tearing of the peroneus longus or brevis, all treated with tendoscopy for peroneal reconstruction and tenorrhaphy. The AOFAS score was obtained by functional assessment during outpatient physical examination. We presented a descriptive analysis of cases, comparing scores over time through the Friedman test followed by Dunn’s test. The relationship between score variations and sex was assessed using the Mann-Whitney test; their comparison with age used Spearman’s linear correlation coefficient. Significance levels were 5%. Results: The AOFAS score showed important improvements such as preoperative scores of 56 and 67 followed by postoperative scores of 100 both in the early and late stages, supporting the efficacy and persistence of this treatment strategy. The p-value obtained after statistical analysis was <0.0001. Conclusion: We concluded that the treatment of foot and ankle comorbidities with tendoscopy, in addition to being less invasive, shows consistency and efficacy as demonstrated by the AOFAS score and functional assessment via postoperative physical examinations. AOFAS scores were increased and maintained at high levels in the postoperative period, demonstrating the efficacy of this procedure and the duration of treatment results. Level of Evidence IV; Case Series; Therapeutic Studies - Investigation of Treatment Results.